2006
DOI: 10.1525/sp.2006.53.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Institutions as Resource Brokers: Childcare Centers, Interorganizational Ties, and Resource Access among the Poor

Abstract: Current theories of how individuals in poor neighborhoods access information and resources have focused primarily on social ties, with concepts such as social isolation dominating discussion. But these theories ignore that individuals often access resources through interorganizational ties. The author suggests that an important role of neighborhood institutions such as churches and childcare centers is to serve as resource brokers-organizations that have ties to businesses, nonprofits, and government agencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
183
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(189 citation statements)
references
References 55 publications
3
183
0
2
Order By: Relevance
“…The more prevalent embeddedness in heterogeneous networks among the higher educated (Ferlander 2007) has, for instance, been linked to assets like employment opportunities (Granovetter 1983;Small 2006). This aspect of social integration has already been discussed in the previous section, as such opportunities are associated with higher incomes and lower job insecurity and their potential role in the association between education and depression.…”
Section: Embeddedness In Cohesive Social Structuresmentioning
confidence: 93%
“…The more prevalent embeddedness in heterogeneous networks among the higher educated (Ferlander 2007) has, for instance, been linked to assets like employment opportunities (Granovetter 1983;Small 2006). This aspect of social integration has already been discussed in the previous section, as such opportunities are associated with higher incomes and lower job insecurity and their potential role in the association between education and depression.…”
Section: Embeddedness In Cohesive Social Structuresmentioning
confidence: 93%
“…As Mouw (2006) stated, "social capital is not an individual characteristic or a personality trait but a resource that resides in the networks and groups to which people belong" (p. 79). Resources refer to any goods that benefit individuals (Lin, 2001;Small, 2006). The study described herein focuses on the types of resources respondents discussed in interviews, those most necessary for the poor (see, e.g., Domínguez & Watkins, 2003;Edin & Lein, 1997;Harknett, 2006): information regarding services such as schools, food banks, and housing assistance; emotional support and validation; help with day-to-day needs like food, transportation, housing, clothing, and child care; help with finding a job; and financial support.…”
Section: Social Capitalmentioning
confidence: 99%
“…In a qualitative study of the brokerage role of child care organizations, child care agencies were found to have a critical role in connecting low-income individuals to community resources. 25 The central placement of the child care/ youth services agencies within these network maps suggests that the agencies' ability to work across ethnic boundaries and link together agencies with different missions may be what makes them effective in helping families access resources.…”
Section: Discussionmentioning
confidence: 99%